Faktor-Faktor Yang Mempengaruhi Kapasitas Petani Milenial Dalam Upaya Percepatan Regenerasi Petani Di Kecamatan Belopa Utara Kabupaten Luwu - Rahmadani S, Adinda Putri; Zainal S, M.; Syafruddin, Syafruddin (Sekolah Tinggi Pertanian Kutai Timur, 2024)
Farmer’s ability is a skill that enables them to set and achieve agricultural goals appropriately. The problem that arises among farmers is the lack of interest of the younger generation in farming in the agricultural sector, due to which the agricultural sector is dominated by older farmers. The purpose of this research is to determine the factors that influence the capacity of millennial farmers as an effort to accelerate farmer regeneration. The research method used is a survey method with a descriptive analysis approach and a quantitative paradigm. Analysis of research data using the SEM model via the Smart PLS application. The research results show that the factors that influence the capacity of millennial farmers are; 1) Internal factors represented by the five indicators in this study include age, formal education, farming experience, cropped area, and length of time in the organization. 2) External factors represented by three indicators including information availability, informal support from leaders and family support. 3) The effectiveness of extension activities is reflected by four indicators, including the skills of instructors, extension media, extension materials and the intensity of extension activities. It can be concluded that internal factors and external factors both have a positive and significant influence on the factors that influence the ability of millennial farmers in their efforts to accelerate farmer regeneration. However, the effectiveness of extension activities has a positive influence on farmers' capacity, although the impact is not statistically significant.